Prevalence and Characteristics of Staphylococcus aureus Isolated From Retail Raw Milk in Northern Xinjiang, China - Kou, Xiaomeng; Cai, Huixue; Huang, Shudi; Ni, Yongqing; Luo, Baolong; Qian, Hao; Ji, Hua; Wang, Xingyi (Frontiers in Microbiology, 2021)
Staphylococcus aureus (S. aureus) is one of the main pathogens causing mastitis in dairy animals worldwide. It is an important opportunistic pathogen of raw milk, and the enterotoxin causes significant food poisoning. Monitoring the antibiotic resistance of S. aureus in raw milk is helpful for a risk assessment of S. aureus. In this study, 62 strains (43.1%) of S. aureus were isolated from 144 retail raw milk samples of different varieties from four regions in northern Xinjiang, China. Among them, the isolation rates at Shihezi, Hami, Altay, and Tacheng were 58.1% (54/93), 12.9% (4/31), 18.2% (2/11), and 22.2% (2/9), respectively. The isolation rate of positive strains in cow milk samples was the highest (61.7%, 37/60), followed by camel milk (35.9%, 23/64), and horse milk (10.0%, 2/20). The results of the classical virulence genes test showed that 12.9% (8/62) of the isolates carried at least one virulence gene. The main genotype was see (6.5%, 4/62), followed by sea+sec (3.2%, 2/62), sea (1.6%, 1/62), and sec (1.6%, 1/62). The analysis of 13 resistance genes and the susceptibility to 12 different antibiotics of 62 isolates showed that 80.6% (50/62) of the strains were resistant to at least one antibiotic, and 46.8% (29/62) were resistant to three or more antibiotics. The isolated strains had the highest resistance rate to penicillin (72.6%, 45/62), and 25.8% (16/62) of the isolates carried the blaZ resistance gene. In addition, 32 strains (51.6%, 32/62) of methicillin-resistant S. aureus were detected. All isolates had the ability to form biofilms. The pulsed-field gel electrophoresis results showed that the 47 isolates revealed 13 major pulsotypes (P1–P13) and 26 subtypes with 80% similarity, indicating the overall genetic diversity in the distribution area and sources of the samples. These findings indicate that S. aureus causes serious pollution of raw milk in northern Xinjiang, which has a negative effect on public health. Therefore, control measures and continuous monitoring should be undertaken to ensure the quality and safety of raw milk.